PENGARUH ANTAGONIS PEMBERIAN KULTUR CAIR Pseudomonas sp. SPESIFIK LOKASI MEUREBO DALAM MENEKAN Fusarium oxysporum PADA TANAMAN CABAI MERAH (Capsicum annum L.) - Agustinur Agustinur; Chairudin Chairudin; Khairul Mustawa (Universitas Teuku Umar, 2020)
Red chili is one of the most widely cultivated horticultural plants. The problem that is often experienced by chilli farmers is wilting caused by Fusarium oxysporum. This disease attacks plant roots and has the potential to cause damage to almost all plant organs. One of the control of these pathogens that can be done is by utilizing biological control agents such as Pseudomonas sp.. This study aims to determine the effect of using crude extract of Pseudomonassp. in suppressing the onset of wilt caused by Fusarium oxysporum on Chili plants. This study used a non factorial randomized block design with a combination of dose and time of administration of Pseudomonas sp. crude extract. The results showed that variations of Pseudomonas sp. crude extract doses was not caused significant effect on the percentage of attacks and the intensity of Fusarium oxysporum attacks. While the best act for the application ofPseudomonas sp. crude extract is when planting. This is significantly different from the application 7 days before and after planting.Keywords: Fusarium wilt disease, Fusarium oxysporum, Pseudomonas sp., Antagonistic, Red Chili